Sclerosing variant of mucoepidermoid carcinoma: a case report and review of literature - S., Radhika; Burad, Deepak; Sonwane, Tushar Yashwant; Vishwanath, Balaji (International Journal of Research in Medical Sciences, 2020)
Mucoepidermoid carcinoma, a malignant tumour of the salivary gland is histologically characterized by the presence of mucoid cells, epidermoid cells and intermediate cells. There are many variants of this tumour. A particular variant, sclerosing variant of mucoepidermoid carcinoma is presented due to its rarity and chances of misdiagnosis as benign lesions due to the presence of extensive sclerosing stroma.